STUDI LUMPUR PEMBORAN MENGGUNAKAN CANGKANG TELUR UNTUK MENGETAHUI RHEOLOGY LUMPUR PEMBORAN PADA TRAYEK 8-1/2´´ HOLE UJI LABORATORIUM - Rante, Wandi Allo; Afifah, Rohima Sera; Kurmaselia, Aprilino Alfa; El Ridlo, Nuruddin Kafy (PETROGAS: Journal of Energy and Technology, 2024)
This study examines the use of water-based mud (WBM) in well drilling. It specifically focuses on enhancing the rheology of WBM that meets API 13A specifications by incorporating calcium carbonate (CaCO3) at concentrations of 2.5% and 7.5%. The primary objective is to compare the original rheology of the WBM adhering to API 13A standards with the modifications following the addition of CaCO3. The methodology employed includes laboratory tests to gather data, testing mixtures of the original mud with added CaCO3, and evaluating the impact on mud properties such as viscosity and density. The results are expected to determine the optimal additive concentration to improve mud performance in drilling operations.